Transjugular Portosystemic Shunting in Refractory Cirrhotic Ascites - Yu. V. Khoronko; M. A. Kozyrevskiy; A. V. Dmitriev; A. A. Volokhova; G. Yu. Spiridenko; K. R. Bogomolova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Improvement of refractory ascites (RA) outcomes in underlying cirrhotic portal hypertension (PH) through optimising the transjugular intrahepatic portosystemic shunting (TIPS) procedure among therapy measures.Materials and methods. The survey included 107 patients with RA admitted to portal hypertension units of the Rostov State Medical University Surgical Clinic during 2007—2020. The patients were randomly assigned to two cohorts similar by gender, age, cirrhosis aetiology and condition severity. The control cohort had conventional paracentesis and albumin infusion. In cohort 2, 57 patients had minimally invasive endovascular TIPS surgery in a recommended setting.Results. TIPS eliminated PH in all 57 patients of cohort 2. Cohort 1 was reported with progressive esophagogastric varices (EGV), their enlargement in 37 and rupture in 11 patients during the first 12 months. Cohort 2 revealed the grade 3—2 and 2—1 EGV reduction in 24 (41.1%) patients with shunt surgery and in 39 (68.4%) patients in one year. Esophagogastric variceal bleeding (EGVB) developed in 9 patients in cohort 1, with 7 lethal outcomes. No variceal bleeding was observed in cohort 2, with 7 patients having the portosystemic shunt dysfunction.Conclusion. The TIPS procedure is justified in cirrhotic PH patients with RA for reducing the mortality rate in a one year follow-up.